From Faith-Based Giving to Development Impact: The Islamic Development Bank’s Global Muslim Philantropy Fund for Children (IsDB’s-GMPFC) and Educational Outcomes in Developing Countries (International Journal of Education and Literature, 2026)
This study investigates how faith-based giving can be transformed into measurable development impact in the education sector, focusing on the Global Muslim Philanthropy Fund for Children (GMPFC) established by the Islamic Development Bank (IsDB) in partnership with UNICEF. Traditional Islamic philanthropic instruments, such as zakat and sadaqah, often provide short-term relief but lack structured governance, limiting their long-term impact on educational outcomes. Using a qualitative-explorative, this research analyzes secondary data from 2021–2025, including institutional reports, program documents, and peer-reviewed literature, to assess how GMPFC operationalizes faith-based resources through pooled, multilateral, and impact-oriented mechanisms. The findings indicate that GMPFC strategically funds education-enabling conditions, including child health, nutrition, psychosocial wellbeing, and youth empowerment, which are empirically linked to school readiness, retention, and learning quality. Comparative analysis shows that GMPFC outperforms traditional philanthropy and conventional aid by combining cultural legitimacy, institutional rigor, and alignment with Sustainable Development Goals (SDGs). Its governance model ensures standardized monitoring, fiduciary oversight, and cross-sectoral integration, addressing longstanding limitations of fragmented philanthropic delivery. Despite its effectiveness, the study highlights a lack of longitudinal learning outcome data, limiting precise quantification of educational impact beyond enabling conditions. Nonetheless, GMPFC exemplifies a hybrid development-finance model, demonstrating how Islamic philanthropic values can be operationalized to generate sustainable, measurable contributions to child education and human capital formation. These findings offer actionable insights for policymakers, development practitioners, and faith-based organizations aiming to scale philanthropic resources for education in vulnerable contexts.